2015
DOI: 10.1017/s0022215114003132
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of sliced tragal cartilage and temporalis fascia in type I tympanoplasty

Abstract: The overall success rate for primary cartilage tympanoplasty is higher when using sliced cartilage than with temporalis fascia grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…In another study, Jiang et al reported significantly better anatomical results with cartilage graft (11). Similar results were published about anatomical outcomes by numerous researchers (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 69%
“…In another study, Jiang et al reported significantly better anatomical results with cartilage graft (11). Similar results were published about anatomical outcomes by numerous researchers (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 69%
“…Khan et al [14] included patients with both “small” and “large” perforations and is by far the largest study, with 390 total patients reported. Kazikdas et al [12], Sishegar et al [15] and Demirpehlivan et al [16] only included subtotal perforations, with the defect being described as more than 50% of the area of the whole tympanic membrane.…”
Section: Resultsmentioning
confidence: 99%
“…First, with the exception of the study by Khan et al [14], which reported on 223 patients, the remaining studies had small cohorts of twenty three to thirty patients in the palisade group. These studies represented the results of single surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous grafts of temporalis fascia are frequently used for ophthalmological, maxillofacial, or otorhinolaryngological procedures, such as orbit and eyelid reconstructions following complex traumas or malignancy,10,11 tympanoplasty,12 nasal septal perforation,13,14 or cerebrospinal fluid leak repair 15. Fascia sampled from other sites, such as fascia lata, are also often employed for eyelid surgery 1618.…”
Section: Discussionmentioning
confidence: 99%